Uma análise crítica da qualidade de águas destinadas ao consumo humano no município de Francisco Beltrão PR - Souza, Lunéia Catiane de (2015)
This research presents a critical analysis on the acceptable levels determined by the brazilian law for water contamination by agro-chemical residues, based on a diagnosis of the quality of water used for human consumption in the city of Francisco Beltrão, state of Paraná. In this work the elements related to the use of natural resources and socio-environmental impacts of agriculture are discuted, emphasizing the issue of water contamination by agro-chemical residues, followed by a diagnosis about the quality of the water in some water bodies in Francisco Beltrão, including microbiological and agro-chemical residues analyses (glyphosate + AMPA, 2,4-D; 2,4,5-T and paraquat). The results obtained by microbiological analyses indicate that from eight analized spots , three community wells and one private well presented contamination by total coliforms, one private water source was contaminated by total coliforms and thermotolerants, also one of the private wells and the water abstracted from one of the collection points used by SANEPAR (Marrecas River) presented contamination in all three parameters (total coliforms, thermotolerant coliforms and Escherichia Coli bacteria). In four of the agro-chemical tests just the one performed in a laboratory presented signals of contamination, although its within the parameters especified by law in the Resolution no. 357, from March 17th, 2005, and the Decree-Law of the Ministry of Health no. 2.914/2011. Even so, the possibility that water with agro-chemical residues can cause damages to humans health along the time must be considered. The other tests didn't present any signs of chemical residues. The result of the agro-chemical tests indicates that none of the samples presents levels over the limit allowed. However, the laboratories are only able to quantify high levels, usually relatively near the limit of the parameters defined by law. We concluded that the maximum levels allowed are questionable and the definition of parameters can be influenced by the great corporations in the food sector, wich obtain the support of the science sector in order to create mecanisms to achieve its interests. After all we understand that the definition of the Maximum Level Allowed by the law is a way to hide the problems caused by the contamination by agro-chemical residues.